HUBUNGAN KECANDUAN GAME ONLINE DENGAN POLA TIDUR PADA REMAJA USIA 16 - 18 TAHUN DI SMA NEGERI 1 DELI TUA KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2019 - Mona Fitri Gurusinga (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Background: online game addiction is one form of addiction that is non-physical, indicated by unhealthy behavior with compulsiveness or continuous behavior in playing online games to get satisfaction so that it will be difficult to stop or limit it even though the behavior causes some social and emotional problems. Method: this study was conducted by Analytical Survey with Cross-Sectional approach. Research Results: there is a relationship between online game addiction and sleep patterns in adolescents aged 16-18 years (value p = 0.004 <α 0.05). Conclusion: adolescents who are addicted to online games with disturbed sleep patterns are more numerous than adolescents who are not addicted to sleep patterns of adolescents who not disturbed. Suggestion: it is expected that all parents pay more attention to their children in using the internet (playing online games), not to be addicted because it will endanger the child's future and the child's sleep patterns will also be disrupted due to lack of sleep.